The yeast Hsp70 Ssa1 is a sensor for activation of the heat shock response by thiol-reactive compounds - Wang, Yanyu (The American Society for Cell Biology, 2012)
The heat shock transcription factor HSF1 governs the response to heat shock, oxidative stresses, and xenobiotics through unknown mechanisms. We demonstrate that diverse thiol-reactive molecules potently activate budding yeast Hsf1. Hsf1 activation by thiol-reactive compounds is not consistent with the stresses of misfolding of cytoplasmic proteins or cytotoxicity. Instead, we demonstrate that the Hsp70 chaperone Ssa1, which represses Hsf1 in the absence of stress, is hypersensitive to modification by a thiol-reactive probe. Strikingly, mutation of two conserved cysteine residues to serine in Ssa1 rendered cells insensitive to Hsf1 activation and subsequently induced thermotolerance by thiol-reactive compounds, but not by heat shock. Conversely, substitution with the sulfinic acid mimic aspartic acid resulted in constitutive Hsf1 activation. Cysteine 303, located within the nucleotide-binding domain, was found to be modified in vivo by a model organic electrophile, demonstrating that Ssa1 is a direct target for thiol-reactive molecules through adduct formation. These findings demonstrate that Hsp70 is a proximal sensor for Hsf1-mediated cytoprotection and can discriminate between two distinct environmental stressors.